The Bonfire of the vanities - De Palma, Brian 1940-; De Palma, Brian 1940-; Hanks, Tom 1956-; Willis, Bruce 1955-; Griffit, Melanie 1957-; Wolfe, Tom 1931- (Warner Home Video, 1990)
Sherman McCoy was Wall Street's Master of the Universe - and everything in his life was right. Then one night he took a wrong turn at the wrong place with the wrong woman. And nothing has gone right since.